ADAPTATION STRATEGY OF TRADITIONAL MARKET TRADERS IN RESPONSE TO DIGITALIZATION COMPETITION - Nasution, Hafizah Mahira; Lubis, Ilham Akbar; Pranata, M. Harry; Siregar, Nurhasanah; Lubis, Sri Nikmah Tullah (Academic Solution Publisher, 2024)
This research discusses how traditional market traders in Pasar Hongkong Medan City adapt to the competition of digitalization. With the increasing penetration of the internet and the popularity of e-commerce, traditional markets face great challenges in maintaining their relevance. The research used a qualitative method with in-depth interviews to traders in three accessories shops as the research subjects. The results showed that the merchants experienced diverse impacts of digitalization. Certain shops successfully utilized technologies such as WhatsApp for digital marketing and transactions, while others faced a decline in revenue. Adaptation efforts involved strategies such as price adjustments, use of social media for promotion, and digital payment systems. This study recommends digital literacy training, market infrastructure improvement, and collaboration with digital platforms to help traditional traders survive in the digital era.